2022
DOI: 10.3390/ijerph19148624
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Cultural Adaptation and Validation of the Fear of COVID-19 Scale for Chinese University Students: A Cross-Sectional Study

Abstract: Background: fear of COVID-19 is widespread among the population, especially among college students because of their increased exposure to the media information overload of the COVID-19 outbreak. The Fear of COVID-19 scale (FCV-19 S) is a relatively short instrument used to evaluate fears surrounding the COVID-19 pandemic. However, the validity and reliability of the Fear of COVID-19 Scale have not been fully investigated in Chinese university student groups. Objectives: this study assessed the cross-cultural a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…According to our results, the level of fear of COVID-19 among Spanish university students was found to be lower than that reported in other studies conducted in the same context in Spain ( 25 , 70 , 71 ). In contrast, other countries have reported higher average scores of fear of COVID-19, including China ( 27 ), Pakistan ( 28 ), Russia and Belarus ( 29 ) and Turkey ( 26 ). Spain was one of the countries in the world most affected by the first wave of the COVID-19 pandemic ( 72–74 ).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…According to our results, the level of fear of COVID-19 among Spanish university students was found to be lower than that reported in other studies conducted in the same context in Spain ( 25 , 70 , 71 ). In contrast, other countries have reported higher average scores of fear of COVID-19, including China ( 27 ), Pakistan ( 28 ), Russia and Belarus ( 29 ) and Turkey ( 26 ). Spain was one of the countries in the world most affected by the first wave of the COVID-19 pandemic ( 72–74 ).…”
Section: Discussionmentioning
confidence: 94%
“…In Spain, the level of fear of COVID-19 among university students ( 25 ) is higher than in other countries such as Turkey ( 26 ), China ( 27 ), Pakistan ( 28 ) or Russia and Belarus ( 29 ). Multiple studies worldwide performed in that population ( 30 , 31 ) have shown the impact that fear of COVID-19 has on several psychological constructs.…”
Section: Introductionmentioning
confidence: 92%
“…Previously it was shown the optimal cutoff scores of the C-FCV-19S was 17.5 [ 30 ]. Based on this criterion, a 59.9% (95% CI: 55.8%–64.0%) prevalence of fear to COVID-19 was found among the current respondents.…”
Section: Resultsmentioning
confidence: 99%
“…Other authors confirm its unifactorial structure, eliminating items (Cassiani-Miranda et al, 2022;Mercado-Lara et al, 2022). Likewise, there is a series of recent publications that stipulate two factors as the structure of FCV-19S, such as Japan (Masuyama et al, 2022); China (Chi et al, 2022;Yang et al, 2022); Hungary (Balázs, Mitev, & Brodszky, 2022); Norway (Iversen et al, 2022) and in Latin America, Ecuador (Moreta-Herrera et al, 2022); Argentina (Caycho-Rodríguez et al, 2022;Furman, Griffiths, Pakpour, & Simkin, 2022) and Peru (Huarcaya-Victoria, 2020).…”
Section: The Scale Of Fear Of Covid-19mentioning
confidence: 92%